Perceived discrimination in ancestral homeland: Filipino nikkeijins and the dynamics of migrant resistance - Vilog, Ron Bridget (Animo Repository, 2012)
The Immigration Control Act of 1990 formally allowed the nikkeijins or descendants of Japanese nationals who were born in foreign countries to enter Japan and work without restriction. Following the rapid migration of Latin American nikkeis, thousands of Filipino nikkeijins had taken advantage of their "ethnic right" by working in Japanese factories. In spite of the privileges bestowed upon them, issues about discrimination, prejudice, and even exploitation had been reported in various fora. This paper examines the reconfiguration of ethnic self-identification as Filipino nikkeijins face social discrimination in Japan. The narratives of second and third generation Filipino nikkeijins reveal that such experiences of prejudice and social stigma had reinforced their nikkeijin identity amidst the dominant Filipino consciousness. The study correlates the experiences of marginalization to the dynamics of migrant resistance and ethnic self-identification.